Pengaruh Metode Pembelajaran Sosial Emosional Terhadap Capaian Belajar Peserta didik Pada Mata Pelajaran Sosiologi Kelas XII IPS 1 - Rasnawia Rasyak; Fatimah Azis (Universitas Lambung Mangkurat, 2024)
Social Emotional Learning is a method that helps students develop their knowledge, attitudes and skills in managing emotions, building healthy relationships, setting goals and making decisions in their lives. The author tried to conduct this research with the aim of finding out the effectiveness of social emotional learning methods in improving student learning outcomes. This type of research uses descriptive qualitative research with research subjects of 34 students in class XII IPS 1. The data collection methods used are observation and questionnaires. Qualitative descriptive data analysis techniques. The research was carried out for two weeks. The results of this research show that there has been an increase in student learning outcomes, where at the first meeting it was seen that students lacked focus when participating in learning activities, there were still many students who were unable to complete the tasks given, but after social emotional learning was carried out at the beginning before learning, it was seen that students can concentrate before learning begins. From the application of the social emotional learning method, it can be concluded that through social emotional learning carried out before the learning process or during the learning process, students' motivation and learning outcomes experience changes and improvements for the better